Students’ Response on the Use of Song in Teaching Listening to the first semester students of Senior High School in Cililin. - Sisdianty Sisdianty; Anifah Anifah (PROJECT (Professional Journal of English Education), 2018)
Listening was the main field of this research. it is due to the importance of this skill to be a basic ability of the students when learning English. Based on the phenomena that student have difficulties in learning english especially listening skill, student could not hear clearly because they do not have good skill in listening. Moreover, we often found they felt bored in learning english especially listening. So, they need some ways to help them in learning listening. The problem in listening can be solved by implementing some techniques. One of them is by using song. The main objective of this study is to knows students’ response on the use of song in teaching listening. This used a qualitative research which involved one class of students as a subject. The instruments were observation sheet and interview. Data analysis shows that the result of the observation and interview done before presented a positiveness of the students’ improvement. They enjoyed learning listening using song and they felt so happy to join the learning process. As a conclusion from the result, teacher needs to consider using song on deliver the material of listening in classroom.